Modeling of national economic system of Belarus and the direction of its transformation - Korotkevich, Aleksei I.; Lapko, Boris V.; Shparun, Dina V. (Journal of the Belarusian State University. Economics, 2018)
In the article is developed a model of national economic system of the Republic of Belarus, using as a model production function Leontiev modified by the authors. Input-output model modification carried out with the aim of creating a toolkit to identify and plan the total cost not only the resources supplied by normal economic activities, but also manpower supplied by households. Resources are considered labour force depending on the occupations. The proposed model allows plan total cost of any of the resources on any kind of final product. The algorithm allows you to build a model of the national economic system on the basis of existing reporting input-output model and statistical data on the labour force and wages.
Keywords: simulation of the national economy; input-output model; the cost of labour; group classes; the total cost of resources; forecasting and planning of the economy